VEGF and Notch in Tip and Stalk Cell Selection - Blanco, Raquel (Cold Spring Harbor Laboratory Press, 2013)
Sprouting angiogenesis is a dynamic process in which endothelial cells collectively migrate, shape new lumenized tubes, make new connections, and remodel the nascent network into a hierarchically branched and functionally perfused vascular bed. Endothelial cells in the nascent sprout adopt two distinct cellular phenotypes—known as tip and stalk cells—with specialized functions and gene expression patterns. VEGF and Notch signaling engage in an intricate cross talk to balance tip and stalk cell formation and to regulate directed tip cell migration and stalk cell proliferation. In this article, we summarize the current knowledge and implications of the tip/stalk cell concepts and the quantitative and dynamic integration of VEGF and Notch signaling in tip and stalk cell selection.